Highly oxidized products from the atmospheric reaction of hydroxyl radicals with isoprene - Torsten Berndt; Erik H. Hoffmann; Andreas Tilgner; Hartmut Herrmann (Nature Communications)
Abstract Isoprene (C5H8) globally accounts for half of the non-methane hydrocarbon flux into Earth´s atmosphere. Its degradation is mainly initiated by the gas-phase reaction with OH radicals yielding a complex system of RO2 radicals. Subsequent product formation is not conclusively understood yet. Here we report the observation of C4- and C5-products from OH + isoprene bearing at least two functional groups. Their production is initiated either by the reaction of initially formed δ-RO2 radicals with NO or by 1,6 H-shift isomerization of Z-δ-RO2 radicals. Both reaction channels also form highly oxygenated molecules (HOMs), which could be important for the generation of secondary organic aerosol. C5H9O8 and C5H9O9 radicals represent the main precursors of closed-shell HOMs. Global simulations revealed that the isoprene-derived HOM-RO2 production is comparable with that of α-pinene, currently regarded as very important HOM source. This study provides a more complete insight into isoprene´s degradation process including the HOM formation.